Study of mechanical, electrochemical, cellular and antibacterial response of Zn2Mg6SiC biodegradable implant - Rai A.; Rai P.; Kumar V.; Singh N.K.; Singh V.K. (My University, 2025)
The present work focuses on the development of a load-bearing biodegradable implant that can apply to repair fractured bones. A novel composite Zn2Mg6SiC was developed via powder metallurgy route and its mechanical, electrochemical and biological properties were studied. A biodegradable implant is imperative to have adequate mechanical strength, better corrosion properties and sufficient biocompatibility. Also, it is expected to sustain its strength until bone healing. In this context, the present work analyses the variation of mechanical properties of Zn2Mg6SiC composite with immersion in SBF for different time durations. Flexural strength, compressive strength, hardness and young's modulus of the composite were sufficient during the immersion period. The corrosion rate of Zn2Mg6SiC depicted from potentiodynamic polarisation was between the ranges of 0.0250 mm/year to 0.0291 mm/year. The Cell cytotoxicity analysis of the composite, performed on osteoblast-like MG-63 cells cultured in incubation media has shown its biocompatibility. Antibacterial tests of the samples were performed for both S. aureus and E. coli bacterias. Results obtained from biological testing have supported the application of the Zn2Mg6SiC composite as a biocompatible implant. SEM, EDS and XRD of the composite in SBF were done to find microstructural changes and elemental concentrations in the composite. © 2020 Elsevier Ltd and Techna Group S.r.l.